2015
DOI: 10.3750/aip2015.45.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Diet and reproduction of the goliath grouper, Epinephelus itajara (Actinopterygii: Perciformes: Serranidae), in eastern Brazil

Abstract: (present address) Freitas M.O., Abilhoa V., Giglio V.J., Hostim-Silva M., Moura R.L., Francini-Filho R.B., Minte-Vera C.V.2015. Diet and reproduction of the goliath grouper, Epinephelus itajara (Actinopterygii: Perciformes: Serranidae), in eastern Brazil. Acta Ichthyol. Piscat. 45 (1): 1-11.Background. The goliath grouper, Epinephelus itajara (Lichtenstein, 1822), is the largest Atlantic grouper. It has been the first marine fish subjected to a fishing moratorium in Brazil (since 2002). The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…PERMANOVA multivariate analyses are being increasingly employed in fish trophic ecology studies (Freitas et al 2015, Pereira et al 2015, Rosa et al 2015 due to their statistical rigor (Anderson and Walsh 2013). This analysis indicated that there were significant differences in the diet of leopard grouper by sex, size, and season, but no significant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…PERMANOVA multivariate analyses are being increasingly employed in fish trophic ecology studies (Freitas et al 2015, Pereira et al 2015, Rosa et al 2015 due to their statistical rigor (Anderson and Walsh 2013). This analysis indicated that there were significant differences in the diet of leopard grouper by sex, size, and season, but no significant interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The data collector asked fishers about the weight of the specimen caught, total length, the fishing gear used, and the catch location. We used body size (weight) to discriminate life stages between juvenile (, 17 kg) and adult individuals ( 17 kg; Freitas et al 2015).…”
Section: Catch Datamentioning
confidence: 99%
“…Longline and spearfishing had the highest averages, while gillnet and trawl had the smallest. The average weight was 7 kg and only 3.4% of the individuals weighed greater than that at the first gonadal maturation (L50 ¼ 25 kg; Freitas et al 2015).…”
Section: Catch Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the food habits of fish are fundamental to understand the structure and functioning of marine ecosystems (Díaz-Ruiz et al 2004;Freitas et al 2015), as they allow us to understand ecological aspects of species such as trophic interactions, their role in the food chain, and the energy flow through ecosystems (Brown et al 2012). They are also extremely important when establishing management plans for species that are exploited due to their economic importance (Rojas-Herrera et al 2004;Moreno-Sánchez et al 2016).…”
Section: Introductionmentioning
confidence: 99%